2021
DOI: 10.3389/fimmu.2021.692079
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating Immune-Related Long Non-Coding RNAs Indicate Prognoses and Response to PD-1 Blockade in Head and Neck Squamous Cell Carcinoma

Abstract: Long non-coding RNAs (lncRNAs) in immune cells play critical roles in tumor cell–immune cell interactions. This study aimed to characterize the landscape of tumor-infiltrating immune-related lncRNAs (Ti-lncRNAs) and reveal their correlations with prognoses and immunotherapy response in head and neck squamous cell carcinoma (HNSCC). We developed a computational model to identify Ti-lncRNAs in HNSCC and analyzed their associations with clinicopathological features, molecular alterations, and immunotherapy respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Having the power to rewrite the regulation network in the tumor-infiltrating immune cells and the TIME ( Uthaya Kumar and Williams, 2020 ; Wells et al, 2020 ), lncRNAs also take part in controlling the immune surveillance, drug resistance and the efficacy of immunotherapy ( Pi et al, 2021 ). Many studies have shown that immune-related lncRNAs were capable of predicting the response for immune checkpoint inhibitor therapy ( Jiang et al, 2020 ; Sun et al, 2020 ; Ma et al, 2021 ; Xu et al, 2021 ; Zhou et al, 2021 ). Consistent with the reported findings, the CRC TRLs signature provided us with immunotherapy treatment indications, showing that patients of the high-risk group were associated with higher expression of cellular receptors targeted by immune checkpoint inhibitor therapy and favorable response towards immunotherapy, which is of great help to stratify CRC patients for immunotherapy ( Bateman, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Having the power to rewrite the regulation network in the tumor-infiltrating immune cells and the TIME ( Uthaya Kumar and Williams, 2020 ; Wells et al, 2020 ), lncRNAs also take part in controlling the immune surveillance, drug resistance and the efficacy of immunotherapy ( Pi et al, 2021 ). Many studies have shown that immune-related lncRNAs were capable of predicting the response for immune checkpoint inhibitor therapy ( Jiang et al, 2020 ; Sun et al, 2020 ; Ma et al, 2021 ; Xu et al, 2021 ; Zhou et al, 2021 ). Consistent with the reported findings, the CRC TRLs signature provided us with immunotherapy treatment indications, showing that patients of the high-risk group were associated with higher expression of cellular receptors targeted by immune checkpoint inhibitor therapy and favorable response towards immunotherapy, which is of great help to stratify CRC patients for immunotherapy ( Bateman, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ben Ma et al developed computational models to identify tumor-infiltrating immune-related lncRNAs (Ti-lncRNAs) in HNSCC and analyzed their relationship with clinicopathological features, molecular changes, and immunotherapy response. They demonstrated Ti-lncRNAs signature was an independent prognostic predictor in HNSCC [ 84 ]. PD-1 expression is associated with methylation in HNSCC.…”
Section: The Role Of Lncrnas In Immunotherapy In Different Tumorsmentioning
confidence: 99%
“…As a monoclonal therapy, PD-1 has been used in the treatment of multiple tumors, including melanoma, and can predict the survival of patients. Recent studies have described the characteristics of tumor infiltrating immune-related lncRNAs (Ti-lncRNAs) and have found a better efficacy of anti-PD-1 treatment in melanoma patients with a low Ti-lncRNA score ( 116 ). WGCNA indicated that 15 lncRNAs, such as NARF-AS1 and LINC01126, were identified to predict the prognosis of melanoma patients treated with anti-PD-1 ( 117 ).…”
Section: Lncrnas As Potential Therapeutic Targetsmentioning
confidence: 99%